2019
DOI: 10.1007/s11606-019-05195-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Health System Experiences with Collaborative Care (CoCM) Billing Codes: a Qualitative Study of Leadership and Support Staff

Abstract: BACKGROUND: Although collaborative care (CoCM) is an evidence-based and widely adopted model, reimbursement challenges have limited implementation efforts nationwide. In recent years, Medicare and other payers have activated CoCM-specific codes with the primary aim of facilitating financial sustainability. OBJECTIVE: To investigate and describe the experiences of early adopters and explorers of Medicare's CoCM codes. DESIGN AND PARTICIPANTS: Fifteen interviews were conducted between October 2017 and May 2018 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Indeed, early adopters of BHI codes have struggled to implement feasible and sustainable staffing, care delivery, and billing practices. 3 Other codes for similar enhanced coordination services (e.g., Chronic Care Management) also experienced low initial take-up, though not to the same extent. 4 This suggests that the structural investments required for BHI services may be particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, early adopters of BHI codes have struggled to implement feasible and sustainable staffing, care delivery, and billing practices. 3 Other codes for similar enhanced coordination services (e.g., Chronic Care Management) also experienced low initial take-up, though not to the same extent. 4 This suggests that the structural investments required for BHI services may be particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Organizationally, practices with low or uncertain BHI service volumes could explore sharing personnel and contract structures with other local practices, and consider how to utilize staff that can deliver and bill for both behavioral health and other types of care management. 3 Use of BHI codes in the first two years was low, but grew steadily. Identifying the characteristics of participating provider organizations, and the clinical utilization patterns of BHI service users, will help inform payment policy and organizational implementation strategies that can support BHI as part of more comprehensive care management infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to consider patients’ active roles in financing care: to what extent is it feasible, equitable, and ethical to use co-pays or other patient payments to fund EBPs? To the extent possible, financing strategies should be straightforward and target the level(s) or system(s) that produce the largest improvements in implementation outcomes; complex strategies may require their own implementation support, as considerable challenges to execution have been observed [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research has identified barriers to using the CoCM codes and a recent study based on a random sample of Medicare beneficiaries found that 0.1% of those with behavioral health conditions received services through either type of code in 2017 and 2018. 3 We expanded on that study to examine the uptake of these codes among a different group of beneficiaries-those with behavioral health conditions attributed to primary care practices, as those with primary care providers are most likely to benefit from these codes. We also examined whether the types of diagnoses and providers differed between CoCM and BHI claims, and if claims were concentrated within practices and states.…”
Section: Introductionmentioning
confidence: 99%